PENGEMBANGAN BAHAN AJAR FUNGSI DENGAN PENDEKATAN ONDE (OPEN ENDED) UNTUK MEMBANGUN KEMANDIRIAN BELAJAR SISWA PADA SISWA MA AL-KHOIRIYAH BALEN - Rita Andika; Dr Junarti; Novi Mayasari (IKIP PGRI Bojonegoro, 2022)
This study aims (1) to create and develop teaching materials with an open ended approach in mathematics at MA Al-Khoiriyah Balan which can be used to build student learning independence. (2) to determine the feasibility and effectiveness of the developed teaching materials. This research includes research development (Research and Development). The model used in this research and development is the ADDIE development model. The research was conducted at MA Al-Khoiriyah Balen majoring in Mathematics and Natural Sciences involving 21 students aiming to find out the effectiveness of functional teaching materials, as well as 2 lecturers and 1 teacher as expert validators to determine the feasibility of teaching materials so that they can be used in learning. The results of the development of functional teaching materials are as follows: the results of the validation of media experts obtained an overall average of 75.4% in the